Human in vivo assessment of the survival and germination of Heyndrickxia coagulans SNZ1969 spores delivered via gummy candies - Susanna Perotti; Giacomo Mantegazza; Elena Pierallini; Natalja Kirika; Robin Duncan; Nicolò Telesca; Andrea Sarrica; Simone Guglielmetti (Current Research in Food Science)
Confectionary products hold promise as unconventional food carriers for probiotic microorganisms. This study explored the delivery of Heyndrickxia coagulans SNZ1969, a spore-forming probiotic, using gummy candies. In this study, we prepared gummy candies containing bacterial spores with a viable count that remained stable during a 24-month shelf-life period, meeting the label claim of at least one billion CFUs per serving (24 g). Then, we carried out an intervention trial involving 24 healthy adults who consumed one serving per day for two weeks followed by an additional two weeks of follow-up. Fecal samples were collected and analyzed with a protocol that allowed the viable counts of SNZ1969, both in spore and vegetative forms. The obtained results revealed that bacterial spores germinated in all volunteers. SNZ1969 persistence in the gut was monitored for two weeks after the end of gummy candy consumption, indicating its potential for prolonged colonization. These findings highlight the potential of unconventional food carriers for probiotic delivery and suggest that spore-forming probiotics can be metabolically active in the human intestine. These findings provide information for the development of food products containing spore-forming probiotics and their potential benefits in promoting gastrointestinal health.